IMPLEMENTASI CLEAN ARCHITECTURE MENGGUNAKAN METODE AGILE PADA PENGEMBANGAN APLIKASI ANDROID: STUDI KASUS BUANG.IN - Anggita Zalsabila, Neng Fia (LPPM Universitas Putera Batam, 2024)
Waste management presents significant challenges that require innovative strategies to improve efficiency and sustainability. Application development has been identified as a potential solution. However, the quality of application code often poses a major hurdle in maintenance and adaptation to change. This study aims to improve the code quality and maintenance of the Buang.in application through the implementation of Clean Architecture. The hope is that implementing Clean Architecture will make the Buang.in application more structured, clear and easy to understand, as well as overcome existing maintenance challenges. In addition, this research aims to provide effective waste management solutions by introducing flexible development options. The limitations of this study include analyzing and improving code quality in the Buang.in application, with a particular focus on implementing Clean Architecture as a code maintenance solution. Changes to the core functionality of the application are not the main focus. By combining Agile and Scrum methodologies, this research adopts adaptive and collaborative software development practices. Agile with Scrum allows development teams to adapt to evolving requirements and prioritize tasks based on highest business value. Therefore, integrating Agile and Scrum in this research ensures that the Buang.in application development process remains efficient and responsive to changes throughout the development cycle.